ANALISIS MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA PT. SUBUR LUMINTU DI SANGATTA KABUPATEN KUTAI TIMUR - Mihani Mihani; Yurdi Maulidani (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
The purpose of this research is to determine and analyze the influence of the Marketing Mix consisting of Product, Price, Distribution and Promotion on Purchasing Decisions at PT. Subur Lumintu Sangatta, East Kutai Regency. The research results show that there is no significant influence between the product variable (X1) on the Purchasing Decision variable (Y). The price variable (X2) has a positive effect on the Purchase Decision variable (Y). There is no significant influence between the distribution variable (X3) on the Purchasing Decision variable (Y). There is no significant influence between the promotion variable (X4) on the price variable (X2). The price variable (X2) has a dominant influence on the Purchasing Decision variable (Y).